HUBUNGAN ANTARA KAMPANYE KANDIDAT KEPALA DAERAH DAN PERILAKU PEMILIH PARTISIPASI POLITIK WANITA (Studi pada Ibu-Ibu Rumah Tangga dalam PelaksanaanPemilihan Kepala Daerah di Kabupaten Sukoharjo) - Gama, Betty; Widarwati, Nunun Tri (Scriptura, 2008)
How does the candidate have to campaign her/his self to be recognized by its citizens? Not all regions have mass media publication, such as newspaper and television. They only have RSPD and private radio station. Therefore, It’s necessarily to carry on the election for the candidate directly in order to be recognized by its citizens. It’s very difficult for the candidate to be recognized by its citizens without campaigning to get maximum result without knowing the voter character. In the marketing field, the product, which has capability to compete and to win the competition, is they, which have capability to fulfill the need, market want, and market expectation. The research uses survey method. The Women political participation is the housewife involvement in voting, while the voter behavior could be observed based on the candidate campaign activity. The data test has been used in this research is Spearmans correlation with the trust level 5%. The Research samples are the housewife in Sukoharjo Regency and living in Sukoharjo district, Bendosari and Polokarto. The sampling technique has been used in this research is multi stage cluster sampling. In this research, campaign is directly the important media for influencing people. Farther, it is necessarily for the candidate to be recognized by citizen their real figure. By the existing support given to district, the society would be tend to behave responsively on the candidate.